Andalusia and heritage: image perceived by visitors: Estudio de bienes y tradiciones destacados por Unesco - Almansa Martínez, Ana; Rodríguez-López, María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The perception that visitors to Andalusia have of the heritage distinguished by Unesco in this community is studied (visitors’ degree of knowledge of this heritage, the means by which they have found out about it, their interest in visiting it and the value they give to this heritage), discovering the image that visitors to the autonomous community of Andalusia have of this heritage. The research technique used was the survey, with a total of 385 respondents. It is worth noting that all of the assets exceeded a score of 3.44 out of 5 in terms of their rating.